BELAJAR MENAVIGASI KETEGANGAN STRATEGIS: PERAN INTERAKSI SOSIAL DALAM MENGEMBANGKAN ENTREPRENEURIAL PARADOX MINDSET (STUDI KASUS KOMUNITAS TDA MAKASSAR) - Muhammad Taufan Gunawan; Andi Tenri Ellyana Haris; Samsinar Samsinar (Jurnal Manajemen Pendidikan, 2026)
Main Objectives: This study aims to explore how informal entrepreneurial communities, specifically Tangan Di Atas (TDA) Makassar, foster an Entrepreneurial Paradox Mindset (EPM) among early-stage entrepreneurs operating outside formal startup accelerator ecosystems. Background Problems: Early-stage entrepreneurs face persistent strategic paradoxes requiring specific cognitive capabilities to navigate. However, empirical research examining EPM development within informal social networks remains limited, particularly in Eastern Indonesia where venture capital access and institutional support are constrained. Novelty: This study identifies the mechanism of "cerot/ cerita otentik" (authentic storytelling) as a emotionally charged, context-rich form of vicarious learning, while demonstrating that frugal innovation serves as a structural necessity rather than merely a strategic choice in resource-constrained regions. Research Methods: Employing an inductive qualitative design following the Gioia methodology, data were collected from 10 early-stage entrepreneurs active in TDA Makassar through in-depth interviews using the Critical Incident Technique, participant observations, and document analysis. Finding/Results: The study uncovers four core strategic paradoxes (Indeterminate Experimentation, Fragmented Persistence, Run while Waiting, and Grow while remaining Small) and highlights the community's role as a cognitive safe space facilitating EPM through authentic narrative sharing and collective reflection.